2019
DOI: 10.1002/jcla.23160
|View full text |Cite
|
Sign up to set email alerts
|

Association between obesity categories with cardiovascular disease and its related risk factors in the MASHAD cohort study population

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made. AbstractBackground: Cardiovascular disease (CVD) is a significant cause of morbidity and mortality globally. Obesity is an important CVD risk factor and is increasing in prevalence. Methods:In this study, 3829 men and 5720 women (35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…They found obese individuals' total daily energy expenditure is lower than non-obese individuals while they intake similar Kcal per day, and almost all the obese subjects formed a sedentary lifestyle. In addition, other studies reported that associated genes, lifestyle, unhealthy diets like high-fat diet [15], and socioeconomic status [16] are account for weight gain as well. This epidemic disease(obesity) can bring about many serious diseases including gallstone disease [17], fatty liver disease, insulin resistance(the main reason for diabetes) [6], hyperlipidemia, hypertension, cardiovascular diseases [15].…”
Section: Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…They found obese individuals' total daily energy expenditure is lower than non-obese individuals while they intake similar Kcal per day, and almost all the obese subjects formed a sedentary lifestyle. In addition, other studies reported that associated genes, lifestyle, unhealthy diets like high-fat diet [15], and socioeconomic status [16] are account for weight gain as well. This epidemic disease(obesity) can bring about many serious diseases including gallstone disease [17], fatty liver disease, insulin resistance(the main reason for diabetes) [6], hyperlipidemia, hypertension, cardiovascular diseases [15].…”
Section: Obesitymentioning
confidence: 99%
“…In addition, other studies reported that associated genes, lifestyle, unhealthy diets like high-fat diet [15], and socioeconomic status [16] are account for weight gain as well. This epidemic disease(obesity) can bring about many serious diseases including gallstone disease [17], fatty liver disease, insulin resistance(the main reason for diabetes) [6], hyperlipidemia, hypertension, cardiovascular diseases [15]. Complications of obesity and obesity itself are highly likely to limit lifespan and increase mortality , especially for older people.…”
Section: Obesitymentioning
confidence: 99%
“…The results of prospective cohort studies have shown that each 5 kg/m 2 higher body mass index (BMI) is associated with a 27% higher risk of chronic heart disease ( 29 ). A cohort study showed an increment in high-density lipoprotein (HDL), low-density lipoprotein (LDL), triglyceride (TG), and total cholesterol (TC) in obese participants ( 30 ). Moreover, a meta-analysis demonstrated LCD can lead to a decrease in body weight, waist circumference (WC), BMI, TG, and blood pressure ( 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…Non‐alcoholic fatty liver disease (NAFLD) is the most common chronic liver disease, which affected one in every three subjects in the developed countries. In spite of being benign in most cases, NAFLD can induce serious injuries, which include inflammation and hepatic necrosis, non‐alcoholic steatohepatitis (NASH), accounting for 20%–30% 1,2 . The risk of liver fibrosis will increase a lot in response to repetitive liver injury from various causes.…”
Section: Introductionmentioning
confidence: 99%